The worship of Confucius - Mumbai Archive Project Team (Jio Institute, 2024)
In Chinese temples, the worship of Confucius involves a blend of ritual offerings, reverential acts, and educational activities. These practices are designed to honour Confucius as a sage and cultural icon, emphasizing his enduring influence on Chinese society and culture.